Behavior of interactions between hydrogen chalcogenides and an anthracene π-system elucidated by QTAIM dual functional analysis with QC calculations12. Issue 51 (22nd June 2017) - Hayashi, Satoko; Sugibayashi, Yuji; Nakanishi, Waro
Abstract : The nature of the interactions between chalcogenides and the anthracene p-system, EH2 -*-p(C14 H10 ), is predicted to be close to that of EH2 -*-p(C10 H8 ), although the partial structures around the central rings can be found in EH2 -*-p(C6 H6 ). Abstract : The nature of EH2 -*-π(C14 H10 ) interactions (E = O, S, Se and Te) of an anthracene system was elucidated by applying QTAIM dual functional analysis (QTAIM-DFA) after clarification of the structural features with quantum chemical (QC) calculations. π-HB (hydrogen bond) interactions were detected for E = O, S, Se and Te, whereas π-EB (chalcogen bond) interactions were observed for E = O in (EH2 )-*-π(C14 H10 ), where the bond paths connected H in EH2 to C14 H10 in π-HB, and they connected E in EH2 to C10 H8 in π-EB. The QTAIM-DFA parameters of ( R, θ ) and ( θ p, κ p ) were evaluated for the interactions via analysing the plots of H b ( r c ) versus H b ( r c ) − V b ( r c )/2 for the interactions at the bond critical points. Data obtained from the perturbed structures around the fully optimized structures were employed for the plots, in addition to the fully optimized structures. Data obtained from the fully optimized structures were analysed using ( R, θ ), which corresponded to the static nature, and those obtained from the perturbed structures were analysed using ( θ p, κ p ), which represented the dynamic nature of the interactions, where θ p corresponds to the tangent line of the plot and κ p is the curvature. The θ and θ p values are less than 90° for all the interactions examined, except for the i H-*- 11 C(π) interaction in TeH2 -*-C14 H10 ( C 1 : IIBAtc ), where i H is located closer to the centre of C14 H10 . Therefore, the interactions examined were predicted to have vdW nature, appeared in the pure-CS (closed shell) interaction region, although i H-*- 11 C(π) was predicted to have the pure-CS/typical-HB nature without covalency. Additionally, the π-HB interaction seems to be slightly stronger than π-EB in (OH2 )-*-π(C14 H10 ).